Effects of construction delays on construction project objectives - M., Abedi (2011)
Delays can be defined as the late completion of works as compared to the planned schedule on the contract. Delays can be avoided or minimized only when their causes are identified. When delay occurred in to our project, it will have adverse consequences on project objectives in terms of time, cost and quality. The aim of the study reported in this paper was to identify the effects of delays that could threat project objectives in construction projects. A comprehensive literature review from various sources through books, conference proceedings, the internet, and civil engineering journals was made to carry out the study. According to delay categories that were contractor related, client related, consultant related, labor related and external related, the results of this study identified the six major effects of delay that were time overrun, cost overrun, dispute, arbitration, total abandonment, and litigation. The study also revealed that time and cost overruns were the frequent effects of delay. It is hoped that this study will become the foundation of further research in the area of project delays and mitigation measures.